The relationship between personal finance practices and productivity of BSN’s employees / Muhamad Khairul Anwar R.M.Kamal - R.M.Kamal, Muhamad Khairul Anwar (Faculty of Business and Management, 2013)
Banking industry is the key players in financial sector and pillars of Malaysia’s economy. In this country, the central bank is Bank Negara Malaysia (BNM). Both bank and finance never can be separated as both correlated each others. This includes Bank Simpanan Nasional (BSN) which is one of the financial institutions operate under development financial institutions (bank under the purview of BNM) category. BSN also one of the government organization besides Employment Provision Fund, Tabung Haji, Lembaga Tabung Angkatan Tentera and others which act as government backbones. Among the purpose of BSN as stated in Bank Simpanan Nasional Act (1974) are (1) to develop and promote savings especially from small savers, and inculcate the habit of thrift and savings, (2) to provide the place of savings especially for public and (3) to utilize the funds of Bank for investment including financing of economic development of the nation. Huat (2009) said that BSN has been an important financial institution for people in rural areas for more than three decades after taking over the role of the Post Office Savings Bank. Moreover, the bank also served as a centre to disburse pension payments to ex-civil servants. Statements above showed how BSN are much needed, so their performance is crucial. In consistent with the performance, their employees‟ productivity inevitably has high impact on it. Crisis always happen and it is only in the corner. So, to remain competitive in this kind of environment, banks will rely even more on their people to make the difference (Bruno-Britz 2009). Besides that Masemola (2003) also had stated that the employer whether private or public, depends mainly on the performance of employees to achieve the mission and vision of the company. Hence, BSN employees need to be productive to ensure the stability and sustainability of the organization. According to Garman (2001) from Masemola (2003) the best employees are typically those who are financially well and the worst are those who are financially unhealthy. Masemola (2003) herself stated her opinion that the prevailing financial problems in employees‟ lives do not create only performance problems but a cycle of personal problems such as including marital problems, family problems, substance abuse, legal action, and divorce. These prove enough if one can manage their personal finance well; it can improve their performance and productivity. As the BSN’s employees are directly deal with all the financial sectors transactions, their knowledge on them should be alright. Practicing the knowledge could be questions. According to New Oxford Dictionary (2007) the definition of practice that most suit this study is to do or take part in regularly or publicly. On the other hand personal finance is use of the principle and techniques of corporate finance in an individual’s money affairs, especially the methods of allocation of financial resources with the objective is financial security and independence so that an individual or a family can meet expected expenses and withstand monetary emergencies (Business dictionary, 2012). Subsequently it can be said personal finance practice is do or take part regularly in individual’s money affairs. Many literatures had been successfully studied on impact of employees money problems towards their employer, the cost incurred to the employer and other factors that affect employees productivity. Nonetheless not much literature discusses on the impact of employees‟ actual personal finance practices on their productivity. Given that, this study wants to explore the reasons of these financial problems to occur among employees with focusing on the personal finance practice.